Does a longer hardening phase improve the plant quality in Prosopis alba Griseb? - Senilliani, Maria Gracia; Guzmán, Analia; Alvarez, Pablo; Brassiolo, Miguel (Instituto de Ecología, A.C., 2022)
The algarrobo blanco tree (Prosopis alba), a tree species used in afforestation in semi-arid zones in Argentina, requires greater knowledge of its growth phases in the nursery to adjust irrigation, fertilization, and plant production time programs, in order to produce quality plants that ensure better responses in the field. For this, in this study, different durations in the hardening phase and their influence on the morphological attributes of quality in Prosopis alba Griseb plants were evaluated. The recorded variables were diameter at neck height (DAC), total height (Ht), root dry weight (PSR) and aerial dry weight (PSA); and the morphological indices: Dickson's index (ICD), aerial and root dry weight ratio (PSA/PSR) and slenderness index (IE). To determine the effects of the treatments tested, longitudinal measurements were made on the DAC and Ht evaluated by repeated means analysis of the mixed linear model’s module. The other parameters were evaluated by analysis of variance in the measurement 105 days after sowing. The results indicated that the treatment with duration of 60 days in the hardening phase presented the morphological parameters with the best quality. It is concluded that a longer duration in the hardening phase generated better morphological attributes, mainly 60% to 140% more root biomass and in the ICD a value 90% to 140% higher with respect to the other treatments.